2019
DOI: 10.1093/bioinformatics/btz035
|View full text |Cite
|
Sign up to set email alerts
|

OLGA: fast computation of generation probabilities of B- and T-cell receptor amino acid sequences and motifs

Abstract: Motivation High-throughput sequencing of large immune repertoires has enabled the development of methods to predict the probability of generation by V(D)J recombination of T- and B-cell receptors of any specific nucleotide sequence. These generation probabilities are very non-homogeneous, ranging over 20 orders of magnitude in real repertoires. Since the function of a receptor really depends on its protein sequence, it is important to be able to predict this probability of generation at the a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
274
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(286 citation statements)
references
References 50 publications
12
274
0
Order By: Relevance
“…We tested this by directly calculating the generation probability of amino acid sequences in the CDR3 to determine if the public clonotypes are easier to generate than the private at both time points, acute and convalescent. This allowed a direct and rigorously quantitative test of whether the expanded persistent public clonotypes were of higher generation probability (39,42). The TCR sequences used by dominant public TCRAV of either GLC-BM-or YVL-BR-specific responses have a significantly greater probability of generation while only the GLC-BM TCRBV public but not the YVL-BR public repertoire has a greater probability of being generated (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We tested this by directly calculating the generation probability of amino acid sequences in the CDR3 to determine if the public clonotypes are easier to generate than the private at both time points, acute and convalescent. This allowed a direct and rigorously quantitative test of whether the expanded persistent public clonotypes were of higher generation probability (39,42). The TCR sequences used by dominant public TCRAV of either GLC-BM-or YVL-BR-specific responses have a significantly greater probability of generation while only the GLC-BM TCRBV public but not the YVL-BR public repertoire has a greater probability of being generated (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We observed uniquely biased V-J usage for each epitope and found that the combined V and J genes in ID clones were largely shared with the SD responses (data not shown). To predict the generation probabilities of ID and SD responses (based on their VDJ recombinations), we made use of the OLGA server (Sethna et al 2019). A per-epitope comparison of the generation probabilities for ID and SD responses did not indicate a significant difference, suggesting that the immunodominance of a T cell clone cannot be explained by high generation probability of its TCR sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Combinatorial pairing of heavy and light chains yields a theoretical diversity of about 2.9 × 10 6 different antibodies. Including the P/N nucleotides, the theoretical number of different antibody sequences is vastly higher than the total number of estimated B cells in the human body (10 12 ) [9]. However, all those antibody sequences are not equally likely to be generated.…”
Section: Introductionmentioning
confidence: 99%
“…However, all those antibody sequences are not equally likely to be generated. Their generation probability spans 30 orders of magnitude for IgH alone [9,10], with additional diversity being generated by insertions and deletions [11]. Of note, due to sampling issues, the number of B cell clones whose size falls below the detection threshold is unknown, rendering estimates of total B cell counts unreliable [12,13].…”
Section: Introductionmentioning
confidence: 99%